The SCARE Statement: Consensus-based surgical case report guidelines. (October 2016) - ,; Afifi, Raafat; Al-Ahmadi, Raha; Albrecht, Joerg; Alsawadi, Abdulrahman; Aronson, Jeffrey; Ather, M. Hammad; Bashashati, Mohammad; Basu, Somprakas; Bradley, Patrick; Chalkoo, Mushtaq; Challacombe, Ben; et al.
Abstract: Introduction: Case reports have been a long held tradition within the surgical literature. Reporting guidelines can improve transparency and reporting quality. However, recent consensus-based guidelines for case reports (CARE) are not surgically focused. Our objective was to develop surgical case report guidelines. Methods: The CARE statement was used as the basis for a Delphi consensus. The Delphi questionnaire was administered via Google Forms and conducted using standard Delphi methodology. A multidisciplinary group of surgeons and others with expertise in the reporting of case reports were invited to participate. In round one, participants stated how each item of the CARE statement should be changed and what additional items were needed. Revised and additional items from round one were put forward into a further round, where participants voted on the extent of their agreement with each item, using a nine-point Likert scale, as proposed by the Grading of Recommendations, Assessment, Development and Evaluations (GRADE) working group. Results: In round one, there was a 64% (38/59) response rate. Following adjustment of the guideline with the incorporation of recommended changes, round two commenced and there was an 83% (49/59) response rate. All but one of the items were approved by the participants, with Likert scores 7–9 awarded by >70% of respondents. The final guideline consists of a 14-item checklist. Conclusion: We present the SCARE Guideline, consisting of a 14-item checklist that will improve the reporting quality of surgical case reports. Highlights: CARE Guideline supports transparency and accuracy in publication of case-reports. However, the CARE guidelines are not tailored to surgery. Delphi-consensus exercise was used to developS urgicalCA seRE port (SCARE) Guidelines. Journals will be encouraged to endorse the SCARE guideline.